2020
DOI: 10.1038/s41598-020-61915-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gait Cycle Loads on Stress Distribution at The Residual Limb/Socket Interface of Transfemoral Amputees: A Finite Element Analysis

Abstract: A Finite Element Analysis (FEA) was performed to evaluate the interaction between residual limb and socket when considering the dynamic loads of the gait cycle. Fourteen transfemoral amputees participated in this study, where their residual limbs (i.e., soft tissues and bone), and their sockets were reconstructed. The socket and the femur were defined as elastic materials, while the bulk soft tissues were defined as a hyperelastic material. Each model included the donning, standing, and gait cycle phase, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…For example, one of the aims of adjustable sockets is to reduce pressures and shear stresses at the stump-socket interface. In line with traditional socket design theory, the adjustable socket adapts to equally distribute pressure across the residual limb, or relieves pressure from sensitive regions by exerting more pressure through more tolerant regions [14,23,[27][28][29]. Furthermore, continuous socket volume adjustments have been shown to promote residual limb volume management [9].…”
Section: Introductionmentioning
confidence: 95%
“…For example, one of the aims of adjustable sockets is to reduce pressures and shear stresses at the stump-socket interface. In line with traditional socket design theory, the adjustable socket adapts to equally distribute pressure across the residual limb, or relieves pressure from sensitive regions by exerting more pressure through more tolerant regions [14,23,[27][28][29]. Furthermore, continuous socket volume adjustments have been shown to promote residual limb volume management [9].…”
Section: Introductionmentioning
confidence: 95%
“…For example, the study by [22] suggested FEM can be classified as an alternative method to evaluate the pre-fabrication prosthetic device. In [23], an investigation of FEA for estimating the dynamic interactions between limb and socket was also introduced. The socket and femur were defined as elastic materials, while the bulk soft tissues were defined as a hyperelastic material.…”
Section: Related Workmentioning
confidence: 99%
“…Residuum health is influenced by intrinsic determinants inherent to personal demographics (e.g., gender, age, weight, and height) and surgical amputation (e.g., length of bone, muscle reassignments, muscle strength, and adipose tissue distribution) and extrinsic determinant-associated attachment (e.g., socket design and direct skeletal attachment) and prosthetic components (e.g., choice and alignment of components, control of the prosthetic joint movements, use of walking aids, and level of activity) ( 8 ). In all cases, interactions between intrinsic and extrinsic determinants are critical as residual tissues have limited physiological capacity to withstand direct loading applied by typical socket-suspended prostheses during daily activities (e.g., chafing and rubbing) ( 5 , 9 12 ). In addition to general neurological residuum and phantom pain, individuals can experience a range of incapacitating neuromusculoskeletal dysfunctions compromising residuum health, such as acute and chronic skin issues, edema, neuroma, tendinitis, muscle contractures, stress fractures, osteopenia, and heterotopic bone growth, which altogether increases the risks of sound lower joints osteoarthrosis, and hyperlordosis ( 6 , 13 , 14 ).…”
Section: Contextmentioning
confidence: 99%